Reading Recent Publications on the Subject of Clemency For ‘Pacification’. Scenes of Transition Justice of the Twentieth Century in Italy in a Comparative Perspective (Italian Review of Legal History, 2020)
Individual clemency - grace - and collective - amnesty and pardon - are at the center of some recent publications, in which the historical perspective is decisive for understanding the meaning of these institutions in the constitutional and penal system, especially in the transition from «Italy land of amnesties» - as Salvemini wrote in 1950 - to today’s eclipse; in fact, the last disputed pardon dates back to 2006, lacking, for the first time, the contextual amnesty. Clemency appears «difficult», «antithesis» rather than «factor» of criminal justice, as it is perceived by public opinion as a spy of the «bad conscience of the legislator» - Radbruch - who, unable to reform the system, is periodically forced to empty the prisons, in a pragmatism without principles, in a ‘state forgiveness’. This public narrative - also fed by jurists between the nineteenth and twentieth centuries - seems to have become ‘common sense’, a prejudice that is difficult to scratch, at the time of criminal populism and its corollaries, including the victim paradigm, for which amnesty would translate into an offense to the victims (Pugiotto). It wasn’t always like this; the «clementia regis, clementia iustitiae» made sense in the ancient regime, which «punished by pardoning and pardoned by punishing»; in the secularized legislative state, legality consists in the application of the law (Lacchè). In Italy the Constitutional Court recommended to the legislator a reversal of the trend in terms of amnesty, the transition from «exceptional instrument to ordinary application» to «ordinary instrument to exceptional application». (Pomanti). After the revision of Article 79 of the Constitution - Constitutional Law 1/1992 - legal basis of the eclipse of the amnesty - a ‘new narrative’ leverages on art. 27, which prohibits treatments contrary to the sense of humanity. The Cedu’s denunciations of the reality of Italian prisons are the basis for the request for deflationary measures, to bring the prison sentence back to the bed of legality, after the hypertrophic imprisonment, registered in the «maximum criminal law» (Anastasia, Corleone, Pugiotto).The years in which the amnesty fulfilled the task of an appropriate criminal policy are long gone; the provisions of 1970, which benefited the crimes committed in the «student year» and in the «hot autumn», adapted the legal system to social reality, in a pacification at the time desired by democratic public opinion (Mazzacuva). The link between political conflict, clemency and the powers of the state is the most studied topic in recent publications on the subject of pardon and amnesty, with particular reference to transitional justice, a historical category that uses a different approach than the traditional continuity / rupture category, which characterizes every historical change (Bianchi Riva). Certain ‘eritage of history’, summary justice or oblivion, also mark our contemporaneity, in search of a way out that is morally and legally negotiated, socially acceptable, from violent and oppressive regimes. Revenge, justice and reconciliation,which in the human soul should be separate, seem «difficult to extricate» (Portinaro). The particularity of the ‘Italy case’ in the context of transitional justice - with the ambiguous intertwining of history, memory, public narration through criminal law - stands out in the light of international comparison, with amnesty linked to experiences of collective violence, from dictatorship to democracy, peace after the war, the ongoing internal conflict (Portinaro, Maculan, Caroli). In the large monograph by the young criminal lawyer Paolo Caroli the Togliatti amnesty - studied in law and in action - is assumed, beyond the intentions, as the starting point of the «Italian amnesic transition», typical of a «country» - in Pasolini’s words - «without memory, which is to say without history». In the constant underlining of the «Italian anomaly» in comparison with the international experiences of transitional justice, Caroli draws, among other things, a comparison between the «criminal law to exit the war and the criminal law to exit Tangentopoli», which - in his opinion - converge in a «de facto impunity». The power not to punish then raises an appropriate question, regarding the attitude of the «criminal instrument to protect memory». As for history, the amnesty, which was controversially called Togliatti, was launched by the De Gasperi Ministry, which ferried Italy from Fascism to the Republic; the presidential decree of 22 June 1946 seems irreducible to a mere «blow in the sponge on fascist crimes» (Franzinelli). The amnesty concerned «crimes, even serious ones, committeddue to a kind of inertia of the anti-fascist insurrectionary movement», and crimes committed by the «young generations», who grew up in fascism, and which the «external and forced discipline» of the regime had made «unable to distinguish good from evil». Togliatti’s words were in tune with the second section of the Supreme Court, which recognized the mitigating factor of the «fascist propaganda» to the ‘boys and girls of Salò’. An outline of the decree of June 22, 1947 deserves consideration; the amnesty, contextual to the launch of the Constituent Assembly, was a profile of the agreement between the main parties; it excluded historical and «eternal» fascism from the horizon of the Constitution; wanted to include all the «good Italians», in an act of «pacification and reconciliation».
Keywords: Clemency and criminal justice; Italy between the nineteenth and twentieth centuries; Transitional justice for ‘pacification’; Amnesties of the winners; Amnesty Togliatti.